Current trends and future prospects of chemical management of oral biofilms - Shankargouda Patil; Vidya GS; Hosam Baeshen; Mohammed Ali Ali Sumayli; Mubarak Ali Saeed AlShahrani; Abdullatif Ibrahim Alkhallaf Najmi; Mohammed Abdurabu Jafer; Satish Vishwanathaiah; Shahrukh Khan (Elsevier, 2020)
Oral biofilm, a tribulation encountered on a general basis is known to associate and contribute to many oral and systemic diseases. Eradication of these biofilms is a primary step in treatment of the underlying malady. Management of a biofilm is governed by various factors: the microenvironment within a biofilm, bond between the adhered surface and the biofilm, location of the biofilm, access to the biofilm for removal. Though annihilation is the priority, the mode of approach to achieve the same is equally important, because biofilm's heterogenic nature and location govern the strategical treatment required. Literature supports that the consequences of oral biofilms is not restricted to its home ground, but disseminated to other systems of the body. This contemplates us to procure knowledge on its development, structure and progression to aim its eradication. Therefore, this review attempts to recognize the type of biofilm based on location and enumerate all the possible chemical modes of management for the specific type of oral biofilms encountered. In addition, to the traditional strategies prescribed or administered, newer approaches which are gaining popularity due to their ease and efficiency are also addressed. Frontiers in the above field, under investigation and promising in near future are also compiled. Thus, the present review aims to provide a comprehensive elucidation of chemical management of oral biofilms, both the conventional and novel approaches under investigation.